Kingdom of the Netherlands-Aruba : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Background Paper describes economic and financial developments in Aruba during 1997-98. The paper highlights that in the mid-1990s, the boom in the hotel sector came to an end, and the economy started to grow at a more sustainable pace. The paper reviews real economic activity, employment, and domestic price movements. It covers public finances and fiscal policy, including the budget for 1999, and also addresses monetary and exchange policy and developments. An analysis of recent trends in the external current and capital accounts is also presented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet